Candidemia in patients with prolonged fever in Kashan, Iran - Reza Razzaghi; Mansooreh Momen-Heravi; Mahzad Erami; Mehdi Nazeri (Mazandaran University of Medical Sciences, 2016)
Background and Purpose: Candida species are considered a common cause of fungal blood stream infections, which are associated with considerable mortality and morbidity rates, especially in the admitted and immunocompromised patients. Despite the increase in new and available antifungal agents, the emergence of resistant strains is growing. Regarding this, the aim of the present study was to assess the fungal epidemiology of candidemia and the antifungal susceptibility patterns against five current antifungal agents among the patients with prolonged fever, who were admitted to Beheshti Educational Hospital, Kashan, Iran. Materials and Methods: This cross-sectional study was conducted on 253 hospitalized patients with prolonged fever despite receiving broad-spectrum antibiotic therapy. Blood samples were collected aseptically, and then cultured using an automated blood culture system and conventional broth culture bottle. Candida isolates were identified at species level using morphological and physiological properties and produced color on the CHROMagar Candida. Furthermore, the antifungal susceptibility testing was performed using (CLSI M27-A3 and CLSI M27-S4) broth microdilution methods. Results: The most positive cultures were detected by the automated blood culture system. C. albicans (%50) was the most prevalent species, followed by C. glabrata (%40), and C. parapsilosis, (%10)  respectively .The mortality rate was high (%60) and most patients with candidemia were admitted to the Intensive Care Unit and Neonatal Intensive Care Unit. All isolates were susceptible to amphotericin B, while the highest resistance belonged to caspofungin. Conclusion: In this study, high resistance was reported, especially for caspofungin, which can be regarded as the emergence of caspofungin-resistant strains. Regarding this, the establishment of a surveillance and prevention program for the reduction of the emergence of resistant species is necessary.